1992
DOI: 10.3109/02656739209021783
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia combined with chemotherapy and irradiation for patients with carcinoma of the oesophagus—A prospective randomized trial

Abstract: From 1988 to 1990, 53 patients with squamous cell carcinoma of the thoracic oesophagus underwent subtotal oesophagectomy after either preoperative hyperthermo-chemoradiotherapy (HCR therapy) or chemoradiotherapy without hyperthermia (CR therapy), in a prospective randomized trial carried out to examine the effects of hyperthermia given preoperatively. The two groups (27 patients given HCR therapy and 26 given CR therapy) were found to be comparable with regard to prognostic factors of age, site of carcinoma, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 12 publications
2
34
0
1
Order By: Relevance
“…In some randomized trials, it has been verified that preoperative chemoradiotherapy improves the survival rate of esophageal cancer patients. Although comparatively few centers perform preoperative chemoradiotherapy because of the high-quality surgical treatment available in Japan, one randomized trial report has shown that hyperthermochemoradiotherapy was effective in the local control of esophageal cancer [53]. There are five meta-analyses based on five to seven randomized trials comparing preoperative chemoradiotherapy followed by surgery with surgery alone.…”
Section: Combined-modality Treatmentmentioning
confidence: 99%
“…In some randomized trials, it has been verified that preoperative chemoradiotherapy improves the survival rate of esophageal cancer patients. Although comparatively few centers perform preoperative chemoradiotherapy because of the high-quality surgical treatment available in Japan, one randomized trial report has shown that hyperthermochemoradiotherapy was effective in the local control of esophageal cancer [53]. There are five meta-analyses based on five to seven randomized trials comparing preoperative chemoradiotherapy followed by surgery with surgery alone.…”
Section: Combined-modality Treatmentmentioning
confidence: 99%
“…Objective tumor regression, histopathological effectiveness of the preoperative regimen and improvement of dysphagia were substantially better in the treatment arm combined with hyperthermia [43]. However, the number of pathological CR with no viable cancer cells in the resected specimens were significantly increased when preoperative radiotherapy was also used in addition to thermochemotherapy ('triple modality') as has been shown in previous trials [44,45].…”
Section: Cancer Of the Esophagusmentioning
confidence: 73%
“…The heat sensitivity of the tumor tissue was higher than that of the adjacent normal tissue, in each case [18]. Patients with carcinoma of the esophagus or of the rec tum are known to benefit from hyperthermia treatment [ 19,20]. A major problem is the application of heat to deeply located lesions.…”
Section: Discussionmentioning
confidence: 99%